Impact of preparatory coronary protection in patients at high anatomical risk of acute coronary obstruction during transcatheter aortic valve implantation. (15th August 2016) - Yamamoto, Masanori; Shimura, Tetsuro; Kano, Seiji; Kagase, Ai; Kodama, Atsuko; Koyama, Yutaka; Watanabe, Yusuke; Tada, Norio; Takagi, Kensuke; Araki, Motoharu; Shirai, Shinichi; Hayashida, Kentaro
Abstract: Background: This study aimed to assess the effectiveness of preparatory coronary protection (CP) in patients considered at high risk of acute coronary obstruction (ACO) after transcatheter aortic valve implantation (TAVI). Methods: The Optimized CathEter vAlvular iNtervention (OCEAN-TAVI) Japanese multicenter registry enrolled 666 consecutive patients. All patients were assessed by preprocedural multidetector computed tomography. CP using a guide wire with or without a balloon was prospectively performed according to the following criteria: 1) coronary height length from the annulus < 10 mm, 2) evidence of ACO during balloon aortic valvuloplasty with simultaneous aortic injection, and 3) shallow valsalva or bulky calcification on the leaflet. The incidence of ACO and other procedural outcomes were compared between the CP and non-CP groups. Results: CP was performed in 14.1% of all patients (94/666). ACO had an incidence of 1.5% (10/666) and mainly occurred in women (70%) and the left coronary artery (70%). The ACO rate was significantly higher in the CP group than in the non-CP group (7.4% [7/94] vs. 0.5% [3/572]; p < 0.001), although notably 30% of ACO were occurred in non-CP group. All 10 ACO cases were successfully treated by catheter intervention, although periprocedural myocardial injury occurred in 42.9% of patients with CP group and 33.3% of those without CP group. Mortality and other periprocedural complications did not significantly differ between the 2 groups. Conclusion: The preparatory CP strategy was feasible for the management of ACO during TAVI, but the complication of ACO was difficult to predict completely.